2018
DOI: 10.1093/cid/ciy426
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dolutegravir Peak Concentrations in People Living With Human Immunodeficiency Virus Aged 60 and Over, and Analysis of Sleep Quality and Cognition

Abstract: DTG Cmax was significantly higher in older PLWH. Our data provides clinicians with key information on the safety of prescribing DTG in older PLWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 34 publications
4
35
0
1
Order By: Relevance
“…Ral-Age study [57•] reported that switching to a RAL-containing regimen in PLWH over 60 years old showed a statistically significant reduction of median values of triglycerides (p = 0.0001) as well as of cholesterol at 36 months of follow-up (p = 0.0023). Significantly increased dosages of DTG were found in patients 9 60 years [26], potentially explaining reported association between age and DTG NP effects.…”
Section: Aging Patientsmentioning
confidence: 80%
See 1 more Smart Citation
“…Ral-Age study [57•] reported that switching to a RAL-containing regimen in PLWH over 60 years old showed a statistically significant reduction of median values of triglycerides (p = 0.0001) as well as of cholesterol at 36 months of follow-up (p = 0.0023). Significantly increased dosages of DTG were found in patients 9 60 years [26], potentially explaining reported association between age and DTG NP effects.…”
Section: Aging Patientsmentioning
confidence: 80%
“…Moreover, some authors found risk factors associated with NP side effects with DTG, with higher risk among women, those aged 60 years and more and those who started abacavir (ABC) at the same time as DTG vs those who did not [11,23,26]. Some data on therapeutic drug monitoring suggest that morning dosing or reducing dosage of DTG could reduce the NP effects [26,27].…”
Section: Neuropsychiatric Symptomsmentioning
confidence: 99%
“…This would suggest an association between dolutegravir C max , rather than AUC or C min , and sleep disorders. A study prospectively designed to ascertain the association between dolutegravir pharmacokinetics and sleep quality found no sleep impairment with higher dolutegravir C max . Not surprisingly, this study dosed dolutegravir in the morning to allow for steady‐state pharmacokinetic measurements.…”
Section: Discussionmentioning
confidence: 79%
“…However, unexpectedly, sleep or cognition changes did not correlate with pharmacokinetics in these older subjects [26]. Higher drug concentrations are universally reported in older people, with a 25% dolutegravir C max increase in people ≥ 60 years old, but increased rates of NPAEs have only been seen in some series [20,25,39]. In agreement with all these data and other series, we did not identify higher dolutegravir-related NPAE rates in older people, a group under-represented in RCTs [43].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation